Fredrik Eens Minne - Hem för ensamma mödrar - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2024)
Fredrik Eens minne is situated at Polhemsgatan, on Kungsholmen in Stockholm, Sweden. The building was ordered by the social democrat and women’s activist Anna Lindhagen. It was the second housing project for single mothers in 1930's Stockholm, which made it a pioneer project. The building is an early example of collective housing, a typology that started and developed during the 20th century. The idea is to have your own apartment or room, and share spaces like kitchen, laundry room or social spaces. There are several examples of collective housing projects in Sweden, mostly in the bigger cities. Regarding the building’s exterior design, we can see a combination of classicism and functionalism. The rustic bottom floor, the ornament above the entrance and a harmonically well proportioned facade show traces of classicism, while the six floors above, with their smooth plaster, window tape and lack of window framing, tell of functionalism. The building was made for single mothers, who could leave their children at the daycare on the top floor, when leaving for work during the day. Today, the building consists of housing and daycare.
Fredrik Eens Minne - Housing for single mothers
Keywords: Female architects/kvinnliga arkitekter; Collective housing/kollektivhus; Funktionalism/functionalism; Daghem/daycare